2021
DOI: 10.1182/blood.2020006329
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyl carboxylase mutations differentially affect the biological function of vitamin K–dependent proteins

Abstract: Gamma-glutamyl carboxylase (GGCX) is an integral membrane protein that catalyzes posttranslational carboxylation of a number of vitamin K-dependent (VKD) proteins involved in a wide variety of physiological processes, including blood coagulation, vascular calcification, and bone metabolism. Naturally occurring GGCX mutations are associated with multiple distinct clinical phenotypes. However, the genotype-phenotype correlation of GGCX remains elusive. Here, we systematically examined the effect of all naturally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 65 publications
0
14
1
Order By: Relevance
“…Another study has previously shown that GGCX mutations can also affect the nonhemostatic VKD proteins MGP and BGLAP differentially. 43 The selective deficiency to γ-carboxylate for example FX or FII for some mutations are new, important findings, which will help to treat respective patients with clotting factor concentrates more efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study has previously shown that GGCX mutations can also affect the nonhemostatic VKD proteins MGP and BGLAP differentially. 43 The selective deficiency to γ-carboxylate for example FX or FII for some mutations are new, important findings, which will help to treat respective patients with clotting factor concentrates more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐responding mutations also affect protein stability as do mutations GGCX:p.(R83P/W) and GGCX:p.(M174R). The loss‐of‐function mutation GGCX:p.(F299S) and the low responding mutation GGCX:p.(S300F) potentially affect vitamin K epoxidation 43 . Patients harboring a low responding mutation in homozygous state or in compound heterozygous state with a loss‐of‐function (GGCX:p.(F299S), GGCX:p.(M174R)), or a nonsense mutation are difficult to treat with vitamin K and result in the most severe hemostatic phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…RNA analysis using either patient blood cells or immortalized lymphoblastoid cells represents an alternative option, providing that the gene of interest is normally expressed in these cells (Wai et al, 2020). In case of the non-feasibility of both approaches, a cell culture-based minigene splicing assay has often been devised (for some most recent examples, see Damasio et al, 2021;Hao et al, 2021;Kim et al, 2021;Kortum et al, 2021;Le Tertre et al, 2021;Morbidoni et al, 2021;Qian et al, 2021;Saint-Martin et al, 2021;Torrado et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Two pathogenic GGCX variants directly affecting this binding site (GGCX:p.(Phe299Ser) and GGCX:p.(Ser300Phe)) resulted in loss‐of‐function for γ‐carboxylation of all analyzed VKD proteins. Both GGCX variants were also found in another study to cause loss‐of‐function or diminished ability to γ‐carboxylate VKD clotting factors (Hao et al, 2021). Hao et al also showed that these two residues show reduced vitamin k epoxidation when mutated.…”
Section: Discussionmentioning
confidence: 70%